2007
DOI: 10.1104/pp.107.096917
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tonoplast Transporters Identified Using a Proteomic Approach with Vacuoles Isolated from Cauliflower Buds

Abstract: Young meristematic plant cells contain a large number of small vacuoles, while the largest part of the vacuome in mature cells is composed by a large central vacuole, occupying 80% to 90% of the cell volume. Thus far, only a limited number of vacuolar membrane proteins have been identified and characterized. The proteomic approach is a powerful tool to identify new vacuolar membrane proteins. To analyze vacuoles from growing tissues we isolated vacuoles from cauliflower (Brassica oleracea) buds, which are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 62 publications
3
51
0
Order By: Relevance
“…The latter study also identified hexokinase in the tonoplast fraction (Carter et al, 2004). Glyceraldehyde 3 phosphate dehydrogenase was present in a proteomic study of vacuoles purified from cauliflower (Brassica oleracea) buds (Schmidt et al, 2007) and also in a barley tonoplast phosphoproteomic study (Endler et al, 2009). Enolase was identified as a protein in highly purified vacuoles from Arabidopsis cell suspensions (Shimaoka et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The latter study also identified hexokinase in the tonoplast fraction (Carter et al, 2004). Glyceraldehyde 3 phosphate dehydrogenase was present in a proteomic study of vacuoles purified from cauliflower (Brassica oleracea) buds (Schmidt et al, 2007) and also in a barley tonoplast phosphoproteomic study (Endler et al, 2009). Enolase was identified as a protein in highly purified vacuoles from Arabidopsis cell suspensions (Shimaoka et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…Evidence for tonoplast localization of glycolytic enzymes in plants has come from a number of independent proteomic studies, although it has been widely ignored as having no functional significance, being attributed to contaminating fractions (Carter et al, 2004) or characterized as soluble cytoplasmic proteins that have no role at the tonoplast (Schmidt et al, 2007;Endler et al, 2009). Triosephosphate isomerase was identified in a proteomic study of barley (Hordeum vulgare) tonoplast (Endler et al, 2006), as well as in the vegetative vacuole proteome of Arabidopsis of both whole vacuoles and tonoplast (Carter et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such studies have also been performed with isolated vacuoles [20][21][22][23] and allowed the identification of new vacuolar membrane proteins. However, these studies do not give any information about changes of the vacuolar membrane proteome occurring in response to changes in environmental conditions.…”
Section: Introductionmentioning
confidence: 99%